Selective C–C bond cleavage of amides fused to 8-aminoquinoline controlled by a catalyst and an oxidant. Issue 89 (20th October 2020) - Li, Sen; Jie, Kun; Yan, Wenjie; Pan, Qingjun; Zhang, Min; Wang, Yufeng; Fu, Zhengjiang; Guo, Shengmei; Cai, Hu
Abstract : Herein, copper-catalyzed direct C–C bond cleavage of amides fused to 8-aminoquinoline as a directing group to form urea in the presence of amines and dioxygen is reported. Abstract : Herein, copper-catalyzed direct C–C bond cleavage of amides fused to 8-aminoquinoline as a directing group to form urea in the presence of amines and dioxygen is reported. Compared to the previous C–H aminations of amides via C–H activation, this reaction presents a catalyst and oxidant controlled C–C bond cleavage strategy that enables amidation through a radical process. CuBr/Ag2 CO3 /O2 shows the best catalytic result at 150 °C. A series of aryl and alkyl amides were compatible with this transformation. Notably, this method provided access to cyclohexanone, one of the most important industrial materials. The pathway of this reaction was investigated.